Effects of physical activity in child and adolescent depression and anxiety: role of inflammatory cytokines and stress-related peptide hormones - Hu, Shaojuan; Li, Xinyuan; Yang, Luodan (Frontiers in Neuroscience, 2023)
Depression and anxiety are the most common mental illnesses affecting children and adolescents, significantly harming their well-being. Research has shown that regular physical activity can promote cognitive, emotional, fundamental movement skills, and motor coordination, as a preventative measure for depression while reducing the suicide rate. However, little is known about the potential role of physical activity in adolescent depression and anxiety. The studies reviewed in this paper suggest that exercise can be an effective adjunctive treatment to improve depressive and anxiety symptoms in adolescents, although research on its neurobiological effects remains limited.